Photoprotective effects of cranberry juice and its various fractions against blue light-induced impairment in human retinal pigment epithelial cells - Chi-Huang Chang; Hui-Fang Chiu; Yi-Chun Han; I-Hsien Chen; You-Cheng Shen; Kamesh Venkatakrishnan; Chin-Kun Wang (Taylor & Francis Group, 2017)
Context: Cranberry has numerous biological activities, including antioxidation, anticancer, cardioprotection, as well as treatment of urinary tract infection (UTI), attributed to abundant phenolic contents. Objective: The current study focused on the effect of cranberry juice (CJ) on blue light exposed human retinal pigment epithelial (ARPE-19) cells which mimic age-related macular degeneration (AMD). Materials and methods: Preliminary phytochemical and HPLC analysis, as well as total antioxidant capacity and scavenging activity of cranberry ethyl acetate extract and different CJ fractions (condensed tannins containing fraction), were evaluated. In cell line model, ARPE-19 were irradiated with blue light at 450 nm wavelength for 10 h (mimic AMD) and treated with different fractions of CJ extract at different doses (5-50 μg/mL) by assessing the cell viability or proliferation rate using MTT assay (repairing efficacy). Results: Phytochemical and HPLC analysis reveals the presence of several phenolic compounds (flavonoids, proanthocyanidin, quercetin) in ethyl acetate extract and different fractions of CJ. However, the condensed tannin containing fraction of ethyl acetate extract of CJ displayed the greater (p < 0.05) scavenging activity especially at the dose of 1 mg/mL. Similarly, the condensed tannin containing fraction at 50 μg/mL presented better (p < 0.05) repairing ability (increased cell viability). Furthermore, the oligomeric condensed tannin containing fraction display the best (p < 0.05) repairing efficiency at 50 μg/mL. Discussion and conclusion: In conclusion, this study distinctly proved that condensed tannin containing fraction of CJ probably exhibits better free radicals scavenging activity and thereby effectively protected the ARPE-19 cells and thus, hampers the progress of AMD.